Pelatihan Kemampuan Resiliensi Pada Mahasiswa Penerima Beasiswa Yayasan X Dalam Menghadapi Tantangan di Kehidupan Sehari-Hari - Kevin Harry Anugerah Cunong; Nurul Aisah; Reinita Nathania; Leticia Virginia Santoso; Muhammad Ridho Darmananda; Indarta Wira; Jenny Lukito Setiawan; Stefani Virlia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2022)
College students have various challenges and problems both in academic life and daily life. The students who become scholarship awardees have pressures with academic targets, regulations, and obligations. It also happens in the X Foundation, scholarship awardees become stressed, anxious, depressed, and have destructive behavior. The challenges faced by college students include self-adaptation, time management, and overthinking planning for further studies and careers in the future. The existence of these problems and challenges causes college students to be less open, pessimistic, hopeless, give up easily, stressed, depressed, and self-harm. Based on these problems, researchers are interested in providing offline training to develop the resilience abilities of student scholarship awardees from X Foundation. From this training collage, students can bounce back in facing difficult situations or problems in daily life. The implementation of the training consists of delivering material, practical activities, reflection, and evaluation. The results of the training showed that there was no significant change in knowledge. However, there is the development of new abilities possessed by college students such as resilience, problem-solving, recognizing self-potential, developing social relations, critical thinking, being proactive, and emotional control that can be applied in daily life.